2019
DOI: 10.1039/c8cp07501h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fullerenol on hIAPP aggregation: amyloid inhibition and mechanistic aspects

Abstract: C60(OH)24inhibits hIAPP aggregation by suppressing the fibril-prone structure and destabilizes hIAPP protofibrils by binding to the amyloid core region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 75 publications
4
31
0
Order By: Relevance
“…Every hIAPP dimer was put in the center of a cubic box with a side length of 6.7 nm. Four C 60 or four C 60 (OH) 8 molecules were displaced in the solvated peptide system at random thus nanoparticle: peptide is 2:1 at molar ratio, which were consistent with previous simulation studies (Bai et al, 2019). The partial charges of oxygen and hydrogen atoms in hydroxyl groups were −0.8 and +0.3, and that of carbon atoms bonded with hydroxyl groups in C 60 (OH) 8 was +0.5, while other carbon atoms were uncharged (Goldsbury et al, 2000).…”
Section: Systemssupporting
confidence: 91%
See 1 more Smart Citation
“…Every hIAPP dimer was put in the center of a cubic box with a side length of 6.7 nm. Four C 60 or four C 60 (OH) 8 molecules were displaced in the solvated peptide system at random thus nanoparticle: peptide is 2:1 at molar ratio, which were consistent with previous simulation studies (Bai et al, 2019). The partial charges of oxygen and hydrogen atoms in hydroxyl groups were −0.8 and +0.3, and that of carbon atoms bonded with hydroxyl groups in C 60 (OH) 8 was +0.5, while other carbon atoms were uncharged (Goldsbury et al, 2000).…”
Section: Systemssupporting
confidence: 91%
“…Both REMD and MD simulations are performed in the isothermal-isobaric (NPT) ensemble at a pressure of 1 bar using GROMACS−4.5.3 software package (Sugita and Okamoto, 1999;Nadler and Hansmann, 2008). We choose OPLS force field TIP4P water molecules, consistent with previous computational studies of hIAPP (Qi et al, 2014;Mo et al, 2016;Bai et al, 2019). hIAPP molecules are kept from the water box at least for 1.0 nm.…”
Section: Remd and MD Simulationsmentioning
confidence: 99%
“…GQDs for in vivo mitigation of T2D amyloidosis.By combining all-atom REMD and MD simulations, AFM and TEM images, ThT and cell toxicity assays, Mo et al[957][958][959] examined the influences of hydroxylated carbon nanotubes and fullerenes on the fibrillization of hIAPP. REMD and MD simulations demonstrated that both CNT-OHs and C60OHs not only suppress the formation of β-sheet and β-hairpin-containing amyloidogenic precursor of hIAPP, but also remodel or disassemble preformed hIAPP protofibrils/fibrils.…”
mentioning
confidence: 99%
“…Turbidity analyses, ThT fluorescence assays, CD microscopies, TEM and AFM images provide direct evidence for the simulation-predicted β-sheet inhibition and protofibril-disruption by hydroxylated CNTs/fullerenes. SH-SY5Y cell viability assays demonstrated the rescue effect of C60OHs on hIAPP-induced cytotoxicity.958 The REMD simulations by Bai et al958,959 showed that C60, C60(OH)8 and C60(OH)24 possess different inhibitory effects on the β-sheet formation of hIAPP: the β-sheet content of hIAPP dimer in the presence of C60, C60(OH)8 and C60(OH)24 is respectively 1.8, 4.2, and 5.6% (the β-sheet content of hIAPP dimer alone is 10.8%). These data reveal that hydroxylation extents modulate the inhibition capacity of C60OHs against hIAPP aggregation.…”
mentioning
confidence: 99%
“…越来越多的研究开始以IDPs作为药 物靶标, 并且已经发现了一些小分子能够结合IDPs [12] . 图 7 (a) hIAPP二聚体结合富勒醇前后的构象系综中聚类最大类的代表结构 [107] ; (b) Aβ42结合HT前后的构象系综 [108] ; (c) c-Myc 402-412 与10058-F4结合态的构象系综 [109] (网络版彩图) Figure 7 (a) The representative conformations for the first most-populated cluster of hIAPP dimer with or without C 60 (OH) 24 [107]; (b) the structural ensembles of Aβ42 with or without HT [108]; (c) the structural ensemble representing the bound state of c-Myc 402-412 and 10058-F4 [109] (color online).…”
Section: 结合过程中存在一个中间体 只有Pkid的两个α-螺旋mentioning
confidence: 99%